A review of aging, degradation, and reusability of PA12 powders in selective laser sintering additive manufacturing. (March 2023) - Yang, Feifei; Zobeiry, Navid; Mamidala, Ramulu; Chen, Xu
Abstract: A popular form of additive manufacturing, selective laser sintering (SLS) enables the unprecedented making of complex 3D parts with high mechanical performance. The semi-crystalline polymer polyamide 12 (PA12) has been extensively used in SLS thanks to its superior mechanical properties, broad sintering window, ease of processibility, reduced warpage and porosity. However, low utilization of the costly feedstock hinders the long-term sustainability of SLS in the industry. Reprocessing and reusing the un-sintered materials with quality assurance have thus appeared as an important and time-sensitive problem. Yet, the feedstocks undergo complex thermal and chemical degradations in SLS. Little results exist to uncover fully the sophisticated process and the reusability of PA12 powders. This review aims to present the state-of-the-art on important aspects of aging mechanisms and degradation behaviors of PA12 powders in SLS. We review first the mechanism of PA12 aging at the molecular scale. Then for the properties of the aged powders, we analyze the evolution of microstructures and geometric properties. Besides, for 3D-printed parts with recycled powders, we cover changes of mechanical properties from tensile strength to Young's modulus. Finally, we provide guidelines and principles of parameter settings when using reclaimed PA12 powders. Graphical Abstract: ga1